2018
DOI: 10.1002/jmv.25311
|View full text |Cite
|
Sign up to set email alerts
|

The nationwide distribution and trends of hepatitis C virus genotypes in mainland China

Abstract: Comprehensive data on hepatitis C virus (HCV) genotypes distribution is critical for treatment regimen selection, vaccine design, and drug development. This study aimed to understand the dynamic distribution of HCV genotypes in Mainland China. Three hundred sixty-two studies published from January 1993 to December 2017 involving 64 891 samples (5133 injecting drug users, 2748 volunteer blood donors, 1509 former paid plasma donors, 160 sexually encounters, and 1992 human immunodeficiency virus (HIV)/HCV coinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…The predominant genotype was 1b (N=29, 48%), followed by 6a (N=10, 17%), 2a (N=6, 10%), 3a (N=6, 10%) and small proportion of 3b, 6 and 1a (Table 5). The distribution of HCV classifications was concordant with a previous national wide investigation of HCV in mainland China, which reported the major HCV genotypes were 1b and 2a, accounting for 54.5% and 16.7%, respectively (35). In our study, 6a was a second major genotype.…”
Section: Resultssupporting
confidence: 88%
“…The predominant genotype was 1b (N=29, 48%), followed by 6a (N=10, 17%), 2a (N=6, 10%), 3a (N=6, 10%) and small proportion of 3b, 6 and 1a (Table 5). The distribution of HCV classifications was concordant with a previous national wide investigation of HCV in mainland China, which reported the major HCV genotypes were 1b and 2a, accounting for 54.5% and 16.7%, respectively (35). In our study, 6a was a second major genotype.…”
Section: Resultssupporting
confidence: 88%
“…In our opinion, the global distribution and prevalence of HCV-genotype 3b have not been defined. However, it has been reported in recent articles that the estimated prevalence rates of HCV subtype 3b in Pakistan and in China are 8.20% and 7.06%, respectively, whereas the frequencies of GT3 cases are significantly higher in South Asia and China (30,31). These results support the notion that upfront genotype testing may be unnecessary before treating HCV-GT3 patients with the SOF/VEL regimen, although the HCV subtype 3b may be suboptimal to it.…”
Section: Discussionsupporting
confidence: 61%
“… 7 China has around 10 million HCV-infected patients, 7 with the most common genotypes being GT1b (52.2–62.8%) and GT2a (16.7–28.7%). 7 , 9 11 GT3 comprises 8.7% to 11.7% of all the local infections, 7 , 9 , 11 with both incidence and prevalence showing an increasing trend in recent years. 10 , 11 For instance, one retrospective study conducted at a hospital in Shanghai, China found that the percentage of GT3-infected patients increased from 13.4% in 2011 to 22.6% in 2014.…”
Section: Hcv Gt3 Epidemiology In Chinamentioning
confidence: 99%
“… 7 , 9 11 GT3 comprises 8.7% to 11.7% of all the local infections, 7 , 9 , 11 with both incidence and prevalence showing an increasing trend in recent years. 10 , 11 For instance, one retrospective study conducted at a hospital in Shanghai, China found that the percentage of GT3-infected patients increased from 13.4% in 2011 to 22.6% in 2014. 12 Geographically, GT3 has spread from the south and southwest regions to the entire country over the last two decades, 11 , 13 albeit with an uneven distribution across different regions; up to 38% of HCV-infected patients in the southwest region are of GT3, while that percentage is only 3% in the northeast region.…”
Section: Hcv Gt3 Epidemiology In Chinamentioning
confidence: 99%